2021
DOI: 10.3390/infrastructures6120171
|View full text |Cite
|
Sign up to set email alerts
|

On the Effectiveness of Vibration-Based Monitoring for Integrity Management of Prestressed Structures

Abstract: In this paper, the effectiveness of vibration-based tests for the detection of damages for prestressed concrete beams is investigated. Despite large research efforts, discrepant and sometimes contradicting conclusions have been drawn regarding the efficacy and reliability of vibration-based monitoring for prestressed structures. Herein, a contribution to this discussion is provided by tackling the problem from a different perspective. Specifically, the question that this paper intends to answer is: “Do vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…The first result is that the first fundamental frequency is affected by the flexural damage, as already well known from the literature (Casas and Aparicio, 1994;Gentile and Saisi, 2007;Venanzi et al, 2020;Pisani et al, 2021). Even if the fundamental frequency is not always highly sensible to damage occurrence, here, Figure 4 shows clearly the variation of this parameter (in the y-axis) with the applied flexural load (in the x-axis), at varying prestress force values.…”
Section: Resultssupporting
confidence: 72%
“…The first result is that the first fundamental frequency is affected by the flexural damage, as already well known from the literature (Casas and Aparicio, 1994;Gentile and Saisi, 2007;Venanzi et al, 2020;Pisani et al, 2021). Even if the fundamental frequency is not always highly sensible to damage occurrence, here, Figure 4 shows clearly the variation of this parameter (in the y-axis) with the applied flexural load (in the x-axis), at varying prestress force values.…”
Section: Resultssupporting
confidence: 72%
“…More recently, Pisani et al 13 numerically studied a series of prestressed RC beams subjected to damage, such as steel corrosion and concrete spalling. Their results showed that reductions of around 10% in the steel strands strength of prestressed beams would lead to 10-fold lower variations in modal frequency values, which were observed to vary in the range of 0.07-1.5%.…”
Section: Effect Of Concrete Cracking/damagementioning
confidence: 99%
“…These results were obtained by considering a loss of steel cross-section along the entire length of the RC elements; if corrosion was instead not assumed as being uniformly distributed throughout the full length of the beam elements, then the variation in frequency values becomes even lower. Pisani et al 13 also studied the case of non-prestressed RC beams, observing higher variation percentages (4-5%) for such elements, which are not subjected to an active state of compression. The authors thus concluded that whilst modal frequency does exhibit a noticeable sensitivity to losses of the tension steel area for reinforced concrete members, the phenomenon becomes essentially negligible for the case of prestressed elements.…”
Section: Effect Of Concrete Cracking/damagementioning
confidence: 99%
See 2 more Smart Citations